Through dialogue towards dialogue: “Classroom management” from a dialogical perspective (Pedagogical Horizons, 2025)
Strengthening young people’s democratic awareness is one of the central tasks of school. From a school theoretical perspective, however, schools can neither ‘create’ democracy nor are they directly controlled by it. Rather, democracy becomes visible in everyday school life: through cooperation, getting to know different perspectives, and jointly searching for and testing possible solutions, answers are found and responsibility is practised. Dialogic education, in the sense of education through dialogue for dialogue, plays a key role in this process by opening up spaces for dialogue with the world, with others and with oneself. Democracy education in schools should therefore enable young people to contribute their experiences to discussions, develop appropriate language, question arguments, listen, and consider social power relations. The way in which conflicts are dealt with in everyday school life, pedagogical attitudes are adopted and spaces for reflection are opened up has a lasting impact on the next generation's understanding of democracy. While democracy education often focuses on knowledge transfer and participation, this article asks how genuine pedagogical action in the sense of dialogical education can contribute to the development of democratic attitudes. Using case studies from current compulsory literature in teacher training, it shows how dialogical learning and empathy create spaces in which democratic attitudes can be promoted.
Keywords: classroom management; dialogic education; democracy education